Polymer based magnetoelectric materials - Martins, P. (2013)
Polymer based magnetoelectric (ME) materials are an interesting and challenging research field, that will bridge the gap from fundamental research to applications in the near future. In the present review, the current state of the art on the different materials, the used configurations for the development of sensors and actuators, as well as the main values of the ME coupling obtained for the different polymer based systems are summarized. Further, some of the specific applications that are being developed for those materials are addressed as well as the main advantages and remaining challenges in this research field.